Eficácia e seletividade de herbicidas isolados e em associações no cafeeiro - Rodrigues, Rafael Jorge Almeida (2017)
Chemical control is the main weed management system in coffee cultivation. However, few herbicides are efficient and at the same time selective to coffee trees. The objective of this work was to evaluate the efficiency of herbicides applied alone and in associations and the their selectivity in the main weeds presents in coffee trees. Two experiments were carried out in randomized blocks with four replications in the municipality of Carmo de Minas (MG - Brazil) in a commercial plantation of the cultivar Catucaí Amarelo 20/15 to evaluate the effectiveness of chemical control in the weed management in the crop line. Firstly, the weed species were identified through the phytosociological profile and, afterwards, post-emergence herbicides saflufenacil (49 g ha-1) and pyrazosulfuron-ethyl (15 g ha-1) were isolated and in association with glyphosate (1080 g ha-1) or sethoxydim (184 g ha-1), plus imazethapyr (100 g ha-1) or chlorimuron-ethyl (15 g ha-1) or flumioxazin (120 g ha-1), respecting the presence of different mechanisms of action in all associations. Percentage of control evaluations were performed at 14, 21 and 28 days after application (DAA) of the treatments. The most important species of weeds were: Digitaria horizontalis, Spermacoce latifolia, Amaranthus retroflexus, Commelina benghalensise Bidens pilosa. In general, associations between herbicides, especially those containing glyphosate, were more efficient at 28 DAA than isolated applications and mixtures containing sethoxydim. The second experiment (of selectivity) was conducted in the coffee sector of the Department of Agriculture of the Federal University of Lavras. Coffee cultivars Topázio MG 1190 were used in a randomized complete block design with four replicates, in which the isolated herbicides saflufenacil (49 g ha-1), pyrazosulfuron-ethyl (15 g ha-1), imazethapyr (100 g ha-1), chlorimuron-ethyl (15 g ha-1), iodosulfuron-methyl (3.5 g ha-1), metsulfuron-methy (6 g ha-1), the latter was used in the associations with the first six herbicides. The phytotoxicity symptoms were evaluated at 7, 14, 21, 28, 35, 42 and 49 days after application (DAA), at 65 DAA the morphological characteristics and physiological variables of gas exchange were determined. It was observed that the herbicides pyrazosulfuron-ethyl, sethoxydim isolated and the mixture between them did not cause symptoms of phytotoxicity up to 49 DAA and did not influence the morphological characteristics and physiological variables, that is, they were selective to the young coffee plants. Mild phytotoxicity symptoms were observed in the isolated applications of imazethapyr and chlorimuron-ethyl at 7 DAA and iodosulfuron-methyl at 14 DAA. With the use of these three herbicides, the stem had a smaller diameter at 65 DAA than the plant without the application. The associations between chlorimuron-ethyl and iodosulfuron-ethyl with sethoxydim promoted phytotoxicity symptoms at 7 DAA and smaller stem diameter respectively. The saflufenacil isolated and in mixture with sethoxydim caused symptoms of visual phytotoxicity of the leaves and smaller diameter of stem in comparison to the control. Methsulfuron-methyl was responsible for late phytotoxicity, negatively interfering with growth and negatively affected the growth of young coffee trees.